Molecular-Dynamics Simulation of Self-Diffusion of Molecular Hydrogen in X-Type Zeolite - Xiaoming Du (Journal of Chemistry)
The self-diffusion of hydrogen in NaX zeolite has been studied by molecular-dynamics simulations for various temperatures and pressures. The results indicate that in the temperature range of 77–293 K and the pressure range of 10–2700 kPa, the self-diffusion coefficients are found to range from 1.61 × 10−9 m2·s−1 to 3.66 × 10−8 m2·s−1 which are in good agreement with the experimental values from the quasielastic neutron scattering (QENS) and pulse field gradients nuclear magnetic resonance (PFG NMR) measurements. The self-diffusion coefficients decrease with increasing pressure due to packing of sorbate-sorbate molecules which causes frequent collusion among hydrogen molecules in pores and increase with increasing temperature because increasing the kinetic energy of the gas molecules enlarges the mean free path of gas molecule. The activated energy for hydrogen diffusion determined from the simulation is pressure-dependent.